2009
DOI: 10.12693/aphyspola.116.733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissipation and Noise on Chaotic Transport in Superlattices

Abstract: We study the effects of dissipation and noise on chaotic electron dynamics, which accompany charge transport in semiconductor superlattices with an applied bias voltage and a tilted magnetic field. We consider the evolution of different chaotic trajectories as decoherence increases, and show that below a critical level of the dissipation rate, dissipative chaos plays an important role in the electron transport. However, by increasing the dissipation rate above the critical level, chaotic dynamics disappear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(70 reference statements)
1
0
0
Order By: Relevance
“…Another topic of practical importance is the effect of disorder on the quantum-classical correspondence. Previously, within a semi-classical picture, we found that although low-amplitude noise has almost no effect on electron diffusion in our system, moderate noise can produce non-trivial phenomena including the enhancement electron mobility 40 . However, there has not been a comprehensive study of these phenomena from a classical perspective, and, to our knowledge, they have not been studied within the quantum realm.…”
Section: Discussionsupporting
confidence: 47%
“…Another topic of practical importance is the effect of disorder on the quantum-classical correspondence. Previously, within a semi-classical picture, we found that although low-amplitude noise has almost no effect on electron diffusion in our system, moderate noise can produce non-trivial phenomena including the enhancement electron mobility 40 . However, there has not been a comprehensive study of these phenomena from a classical perspective, and, to our knowledge, they have not been studied within the quantum realm.…”
Section: Discussionsupporting
confidence: 47%